Model essays for ielts writing (Tổng hợp, 2014)
Contents: In the past, people spent their entire lives doing one job; What are the main tasks of universities; Should the government pay for medical care and education? Why?; What is it in the mass media that has egative effects on teenagers and what meas- ures should governments take to solve this problem.